Fluctuations in phenylalanine concentrations in phenylketonuria: a review of possible relationships with outcomes - Cleary, Maureen; Trefz, Friedrich; Muntau, Ania C.; Feillet, François; van Spronsen, Francjan J.; Burlina, Alberto; Bélanger-Quintana, Amaya; Giżewska, Maria; Gasteyger, Christoph; Bettiol, Esther; Blau, Nenad; MacDonald, Anita (Molecular genetics and metabolism, 2013)
Fluctuations in blood phenylalanine concentrations may be an important determinant of intellectual outcome in patients with early and continuously treated phenylketonuria (PKU). This review evaluates the studies on phenylalanine fluctuations, factors affecting fluctuations, and if stabilizing phenylalanine concentrations affects outcomes, particularly neurocognitive outcome. Electronic literature searches of Embase and PubMed were performed for English-language publications, and the bibliographies of identified publications were also searched. In patients with PKU, phenylalanine concentrations are highest in the morning. Factors that can affect phenylalanine fluctuations include age, diet, timing and dosing of protein substitute and energy intake, dietary adherence, phenylalanine hydroxylase genotype, changes in dietary phenylalanine intake and protein metabolism, illness, and growth rate. Even distribution of phenylalanine-free protein substitute intake throughout 24h may reduce blood phenylalanine fluctuations. Patients responsive to and treated with 6R-tetrahydrobiopterin seem to have less fluctuation in their blood phenylalanine concentrations than controls. An increase in blood phenylalanine concentration may result in increased brain and cerebrospinal fluid phenylalanine concentrations within hours. Although some evidence suggests that stabilization of blood phenylalanine concentrations may have benefits in patients with PKU, more studies are needed to distinguish the effects of blood phenylalanine fluctuations from those of poor metabolic control.